2001
DOI: 10.1016/s0028-3932(00)00135-4
|View full text |Cite
|
Sign up to set email alerts
|

Variability of response times as a marker of diverted attention

Abstract: propose that this lack of consistency is an important determinant of patients' behaviour, and may result from a deficit independent of other mechanisms causing neglect. Here we suggest that an increase of variability, and not only of RTs, is to be expected when attention is exogenously biased away from the probed location. Consequently, space-based variability can be interpreted in the framework of existing models of unilateral neglect. According to one such model, a basic impairment in left neglect is a bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Right IPL lesions produce neglect of the contralateral hemifield. But even here, a gradient of IIV can be observed with performance variability greatest for the most eccentric locations (Anderson and others 2000; Bartolomeo and others 2001). …”
Section: Individual Variability and Disorders Of Attentionmentioning
confidence: 73%
“…Right IPL lesions produce neglect of the contralateral hemifield. But even here, a gradient of IIV can be observed with performance variability greatest for the most eccentric locations (Anderson and others 2000; Bartolomeo and others 2001). …”
Section: Individual Variability and Disorders Of Attentionmentioning
confidence: 73%
“…Recall that in this experiment cues were peripheral and non-informative, thus eliciting an exogenous attentional shift. The re-analysis [114], whose results are displayed in Fig. 7, showed that, for normal individuals, invalid trials yielded less consistent response times than valid trials at short (150 ms) SOA, that is, the time interval most likely concerned with exogenous attentional shifts.…”
Section: Impaired Orienting Of Attention In Neglect: Exogenous Vs Enmentioning
confidence: 97%
“…Some studies have also observed that the speed of response tends to be rather variable in these neglect patients [2,5,60]. One interesting phenomenon is that, despite the fact that a patient's response is generally slow, one occasionally observes rather fast RTs to left-sided targets.…”
Section: Introductionmentioning
confidence: 98%
“…One interesting phenomenon is that, despite the fact that a patient's response is generally slow, one occasionally observes rather fast RTs to left-sided targets. This may not be surprising if we do not simply view the damage to attention as an all-or-none phenomenon, so that the actual probability of a left target of capturing attention is never zero [2,5]. Indeed, it is now clear that spatial attention is modulated by other more general attentional factors, such as arousal or alertness [74][75][76]80].…”
Section: Introductionmentioning
confidence: 99%